Profile of Junior High School Students and Parents Knowladge abaut Adolescent Reproductive Health in SMP Negeri 3 Pariaman - Rosha Noviana; elsa yuniarti; Sa'adiyatul fuadiyah; Rahmawati D Rahmawati D (Universitas Negeri Padang, 2020)
Reproductive health is condition of physical, mental, and social as a whole, not merely the absence of disease or infirmity, but in all aspects related to the reproductive processes functions and system at all stages of life. Knowledge of reproductive health have to know in early by the teenagers, but in the reality still have many teenagers not know reproductive. Based on the observation in SMPN 3 Pariaman shown case about reptoductive health. It is because teenagers don’t know effect of their action. The research used is descriptive research to know the description of student and parents knowledge abaout adolescent reproductive health in SMPN 3 Pariaman. Population were all students at grade VII and VIII and parents of student from 14 class. The sample technique used is random sampling. Proportionate proportionate stratified random sampling type.The instrument is knowledge test about teenagers of reproductive health. Besed on this research, the knowlwdge level of the students and parents is medium category, they are 55,6% and 70%. Another that, sex and parents educations is also influence on their knowledge about 23,1% and 21,4% and they have relate between students knowledge and their parents in SMP Negeri 3 Pariaman.